2015
DOI: 10.1039/c5ra16583k
|View full text |Cite
|
Sign up to set email alerts
|

Novel LDPE/halloysite nanotube films with sustained carvacrol release for broad-spectrum antimicrobial activity

Abstract: The emergence of antibiotic resistance of pathogenic bacteria has led to renewed interest in exploring the potential of plant-derived antimicrobials e.g., essential oils (EOs), as an alternative strategy to reduce microbial contamination. However, the volatile nature of EOs presents a major challenge in their incorporation into polymers by conventional high-temperature processing techniques. Herein, we employ halloysite nanotubes (HNTs) as efficient nano-carriers for carvacrol (a model EO). This precompounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 76 publications
6
55
2
Order By: Relevance
“…Further advantages of polymeric antibacterial agents are that they are non‐volatile, chemically stable, and have low penetration through the skin . These polymeric antimicrobial agents could be utilized in a variety of applications such as water treatment, food packaging, sanitary, medical applications, and health care‐related materials …”
Section: Introductionsupporting
confidence: 82%
“…Further advantages of polymeric antibacterial agents are that they are non‐volatile, chemically stable, and have low penetration through the skin . These polymeric antimicrobial agents could be utilized in a variety of applications such as water treatment, food packaging, sanitary, medical applications, and health care‐related materials …”
Section: Introductionsupporting
confidence: 82%
“…Adsorption of EOs into an inorganic porous material was proposed as a technique that could provide a controlled release of EOs into the polymeric matrix and stabilize this hybrid polymer. In the last years there has been an increasing interest in the development of food packaging materials based on polymer/EO/clay nanocomposites where the EO has been initially introduced into clay structure (Barbosa‐Pereira, Angulo, Lagarón, Paseiro‐Losada, & Cruz, ; Busolo & Lagaron, ; Campos‐requena, Figueroa, & Sanfuentes, ; Shemesh et al, ; Tornuk, Hancer, Sagdic, & Yetim, ). Nevertheless, there are few literature reports which mention the use of biopolymer instead of polymer matrix for the development of such materials (Abdollahi, Rezaei, & Farzi, ; Campos‐Requena et al, ; Gomes et al, ; Klangmuang & Sothornvit, ; Pires, de Souza, & Fernando, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of remaining concentrations of carvacrol in the films, immediately following synthesis and hot pressing, has shown that approximately 70% is retained after the processing steps, comparable with other inorganic/polymer composites used for essential oil controlled release materials . The average final film concentration of carvacrol was 1.74 wt% ± 0.19 ( n = 15).…”
Section: Resultsmentioning
confidence: 62%
“…The effectiveness in the retention of carvacrol in nanocomposite films was compared with neat LDPE films by measuring the diffusion coefficients in both materials. The diffusion coefficients were calculated from the initial linear slope of the fractional mass release ratio versus square root of time ( m t / m ∞ versus t 1/2 ) by using Eqn : mttrue/m=0.25em4Dt/πl21true/2 where m t is the amount of carvacrol released at time t , m ∞ is the amount of carvacrol released at equilibrium, l is the thickness of the film and D is the diffusion coefficient. Figure (a) shows different release profiles for neat LDPE films with carvacrol and LDPE/OMM nanocomposites with carvacrol.…”
Section: Resultsmentioning
confidence: 99%